Thanksgiving - Evanovich, Janet (HarperTorch fiction., 2006)
When Megan Murphy discovers a rabbit gnawing on the hem of her skirt, she is about to give its careless owner a piece of her mind, but Dr. Patrick Hunter turns out to be too attractive to be mad at.